2017
DOI: 10.1002/er.3887
|View full text |Cite
|
Sign up to set email alerts
|

Thermal management and catalytic combustion stability characteristics of premixed methane/air in heat recirculation meso-combustors

Abstract: Summary In order to illuminate heat recirculation effect on catalytic combustion stability and further improve energy conversion efficiency in meso‐combustor, the catalytic combustion characteristics of the combustor with/without preheating channels are numerically studied at steady conditions. It is found that methane conversion rate and combustion efficiency increases by 2% to 3% and approximately 9% in the heat recirculation meso‐combustor, indicating that heat recirculation effect facilitates more complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The methane conversion rate is a parameter that can be used to evaluate the length of the combustion chamber required for complete combustion. In this study, the methane conversion rate is defined as the ratio between the mass fraction of methane converted at the middle of the combustion chamber ( x = 0.477 m) and the mass fraction of the inlet methane, which is expressed by equation (27) 46 …”
Section: Numerical Results and Analysismentioning
confidence: 99%
“…The methane conversion rate is a parameter that can be used to evaluate the length of the combustion chamber required for complete combustion. In this study, the methane conversion rate is defined as the ratio between the mass fraction of methane converted at the middle of the combustion chamber ( x = 0.477 m) and the mass fraction of the inlet methane, which is expressed by equation (27) 46 …”
Section: Numerical Results and Analysismentioning
confidence: 99%
“…3,4 Based on high energy density of hydrocarbon or hydrogen fuel, micro-and mesoscale combustion has a wide range of potential applications. [5][6][7] However, due to tiny size and large surface-to-volume, the micro-combustor faces the challenges of large heat loss and flame instability. In MTPV system, micro-combustor as the important component plays a key role in maintaining flame stability and energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…3 In fact, an enormous amount of unorganized VOCs emissions directly jeopardize the normal growth of fauna and flora, 4,5 as well as form the important precursors 6,7 of ozone and secondary aerosols, which could contribute secondary pollution and even lead to more serious destruction to environment and organism. Nowadays, adsorption, 8,9 combustion oxidation, [10][11][12][13][14] and biodegradation 15 all have been widely used in the treatment of VOCs treatment, and catalytic combustion is one of the most vital methods in reducing VOCs. 16 Aiming at the catalytic oxidation for VOCs, de Rivas et al, 17 respectively, performed the experimental studies on VOCs over six various kinds of Ce-Zr catalysts, which indicated the catalysts with mole ratio 0.15:0.85 and 0.5:0.5 have the best stability.…”
Section: Introductionmentioning
confidence: 99%